Oxygen consumption rate of Caenorhabditis elegans as a high-throughput endpoint of toxicity testing using the Seahorse XFe96 Extracellular Flux Analyzer - Preez, G Du; Fourie, H; Daneel, M; Miller, H; Höss, S; Ricci, C; Engelbrecht, G; Zouhar, M; Wepener, V (Scientific reports, 2020)
Caenorhabditis elegans presents functioning, biologically relevant phenotypes and is frequently used as a bioindicator of toxicity. However, most C. elegans in vivo effect-assessment methods are laborious and time consuming. Therefore, we developed a novel method to measure the oxygen consumption rate of C. elegans as a sublethal endpoint of toxicity. This protocol was tested by exposing 50 larval stage one C. elegans individuals for 48 h (at 20 °C) to different concentrations of two toxicants i.e. benzylcetyldimethylammonium chloride (BAC-C16) and cadmium (Cd). Following exposures, the oxygen consumption rate of the C. elegans individuals were measured using the high-throughput functionality of the Seahorse XFe96 Extracellular Flux Analyzer. Dose-response curves for BAC-C16 (R2 = 0.93; P = 0.001) and Cd (R2 = 0.98; P = 0.001) were created. Furthermore, a strong, positive correlation was evidenced between C. elegans oxygen consumption rate and a commonly used, ecologically relevant endpoint of toxicity (growth inhibition) for BAC-C16 (R2 = 0.93; P = 0.0001) and Cd (R2 = 0.91; P = 0.0001). The data presented in this study show that C. elegans oxygen consumption rate can be used as a promising functional measurement of toxicity.
Keywords: Caenorhabditis elegans; Mitochondria; Hazardous Substances; Smegmamorpha; průběh práce; Workflow; vztah mezi dávkou a účinkem léčiva; Food Safety; rychlé screeningové testy; spotřeba kyslíku; Oxygen Consumption; Animals; lidé; Toxicity Tests; Humans; zvířata; High-Throughput Screening Assays; testy toxicity; Environmental Exposure; bezpečnost potravin; nebezpečné látky; kadmium; Dose-Response Relationship, Drug; mitochondrie; vystavení vlivu životního prostředí; Cadmium